Compositional effect in pentagonal layered PdSe2-xSx solid-solutions and their transport properties. (June 2020) - Ryu, Jung Hyun; Lee, Kyu Hyoung; Hong, Seok-won; Hwang, Jeong Yun; Yi, Yeonjin; Im, Seongil; Kim, Sang-il; Kim, Se Yun; Lee, Kimoon
Abstract: Authors report the synthesis of PdSe2- x S x solid-solutions (0 ≤  x  ≤ 0.86) with pentagonal layered structure and their transport properties. From structural and optical characterizations, it can be confirmed that S atoms are successfully substituted on Se-site in the parent phase of PdSe2 . By analyzing the electrical and thermal transport characteristics, it reveals that the density of states effective mass as well as band gap of PdSe2- x S x can be controlled by varying x . It strongly suggests that S substitution can be an effective compositional tuning approach for engineering the electronic band structure in pentagonal layered PdSe2 system. Graphical abastract: Image, graphical abstract